Pelatihan Pembuatan Laporan Keuangan Menggunakan Aplikasi Excel Pada Umkm Usaha Dagang R3 Di Kota Batam - Syarif Hidayah Lubis; Ni Putu Winda Ayuningtyas; Hardi Bahar (LPPM Universitas Putera Batam, 2023)
MSME is one type of business that really needs financial reports because it invites strategic elements in the structure of the national and regional economy but is a Trading Business Partner (UD) R3 as MSMEs do not yet have financial reports so they do not know the benefits that have the potential to not continue the business. The purpose of this service is to provide counseling about financial reports and procedures for making financial reports using the excel application. The expected output target is the ability of the R3 Trading Business (UD) to prepare financial reports that comply with standards. The output is aimed at partners being able to understand financial reports and being able to make standard and practical financial reports using the Excel application. The results of the dedication show that UD R3 has been able to make standard and practical financial reports using the excel application, has been able to understand the basics of financial reports and their benefits so that in the end partners are able to prepare their own financial reports for their business, can practice directly by inputting each transactions for sales or purchases with Directions from the service team, can recognize computer applications in the form of excel which have been formulated so that every UD R3 partner transaction only makes a journal and finally obtains the necessary financial reports, can understand financial reports produced in practice which have been directly guided by the service team.